2001
DOI: 10.3102/00028312038003499
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Turnover and Teacher Shortages: An Organizational Analysis

Abstract: Contemporary educational theory holds that one of the pivotal causes of inadequate school performance is the inability of schools to adequately staff classrooms with qualified teachers. This theory also holds that these school staffing problems are primarily due to shortages of teachers, which, in turn, are primarily due to recent increases in teacher retirements and student enrollments. This analysis investigates the possibility that there are other factors-those tied to the organizational characteristics and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

64
1,704
5
71

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,863 publications
(1,942 citation statements)
references
References 37 publications
64
1,704
5
71
Order By: Relevance
“…This has meant that, unfortunately, children in countries needing teachers the most, tend to be taught by the least qualified personnel (UNESCO, 2006). In contrast, in the developed world, such as the USA, the UK and many European countries, shortage of teacher supply tends to be a particularly pressing problem for core subject areas such as maths, modern foreign languages and science (European Commission, 2012) and for schools serving socioeconomically deprived communities (Ingersoll, 2001;Guarino et al, 2006;Boyd et al, 2008). Grissom's (2011) study found that higher teacher turnover rates in disadvantaged schools result in part from the ineffectiveness of the principal.…”
Section: Teacher Retention: Quality Mattersmentioning
confidence: 99%
“…This has meant that, unfortunately, children in countries needing teachers the most, tend to be taught by the least qualified personnel (UNESCO, 2006). In contrast, in the developed world, such as the USA, the UK and many European countries, shortage of teacher supply tends to be a particularly pressing problem for core subject areas such as maths, modern foreign languages and science (European Commission, 2012) and for schools serving socioeconomically deprived communities (Ingersoll, 2001;Guarino et al, 2006;Boyd et al, 2008). Grissom's (2011) study found that higher teacher turnover rates in disadvantaged schools result in part from the ineffectiveness of the principal.…”
Section: Teacher Retention: Quality Mattersmentioning
confidence: 99%
“…Le rapport au métier au cours des dernières années, une abondante littérature a été consacrée au malaise enseignant (Bourdoncle & demailly, 1998 ;Maroy, 2006) et à l'abandon volontaire (ingersoll, 2001 ;Johnson, Berg, & donaldson, 2005 ;ocde, 2005). Plusieurs auteurs s'accordent sur le fait que le stress et l'épuisement professionnel des enseignants (Maslach & Jackson, 1986), la violence verbale et physique des élèves, les classes difficiles (Barrère, 2002) comme le fait remarquer hargreaves (1998,2000), au coeur de l'exercice du métier d'enseignant se trouvent les émotions qui, selon qu'elles sont positives ou négatives, augmentent ou réduisent le moral professionnel (collie, shapka, & Perry, 2011 ;lison & de Ketele, 2007).…”
Section: Les Facteurs Institutionnelsunclassified
“…la dimension extrinsèque correspond aux réactions de l'individu face aux caractéristiques de l'éta-blissement ou de son organisation reliées aux aspects suivants : le leadership de la direction, la qualité et la quantité des ressources matérielles disponibles, la réputation de l'établissement scolaire, le comportement et la performance scolaire des élèves, le climat de sécurité au sein de l'école et de la classe, la taille de la classe, la qualité des locaux, le volume des tâches ainsi que les activités de développement professionnel (collie et al, 2012 ;dinham & scott, 1998Fresko, 1997 ;rieg, Paquette, & chen, 2007). aussi, certains auteurs étasuniens ont évoqué l'insuffisance de soutien de la part des autorités et des collègues comme facteur principal du sentiment d'inefficacité (Betoret, 2007 ;ingersoll, 2001 ;sass et al, 2011 ;shachar, 1997). la satisfaction extrinsèque inclut en outre le salaire, la rente de retraite, les primes, les vacances, la reconnaissance publique et la valorisation sociale de la profession, ainsi que certaines conditions spéci-fiques de travail telles qu'une classe bien éclairée et aérée ou un stationnement sécuritaire (Johnson et al, 2005).…”
Section: Les Facteurs Institutionnelsunclassified
“…Attempts by states and districts to retain these new teachers have only achieved pockets of success as novice teachers generally leave the profession within three to five years. These teachers often leave jobs in low performing schools seeking jobs in higher-performing schools or leaving the profession altogether (Ingersoll, 2001(Ingersoll, , 2011Ingersoll & Merrill, 2013). The most vulnerable schools continue to lose teachers as the majority of teachers seek assignments in schools where students are easy to teach (Clotfelter, Ladd, Vigdor, & Aliago-Diaz, 2004;Ingersoll, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Although the rate of teacher turnover is comparable to that of police officers it is higher than the turnover rate in other highly regarded professions such as nursing, law, architecture, engineering, and academia (Ingersoll & Perda, 2012). While adequate numbers of teachers are being produced and hired, an even larger number vacate the profession every year for reasons other than retirement (Ingersoll, 2001(Ingersoll, , 2003.…”
Section: Introductionmentioning
confidence: 99%